2018
DOI: 10.4071/imaps.661015
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Novel Ceramic Encapsulation Materials for Electronic Packaging

Abstract: Enhancements on power electronic systems with reduced chip area and miniaturized passive components are subject of several research activities in academics and industry. To realize such future electronic devices, it is necessary to incorporate wide bandgap semiconductor technology such as silicon carbide and gallium nitride operating at higher temperatures. Therefore, the development of novel materials with high thermal conductivities and stability, withstanding harsh environments up to 300°C is of major inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, several problems using these inorganic encapsulations were identified. Among them were corrosion of the metals, water uptake, limited potting time, and limited adhesion [8]. While corrosion of the metals and the water uptake could be reduced by measures concerning the recipe of the encapsulation, the potting time and the adhesion remain a bottleneck.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…However, several problems using these inorganic encapsulations were identified. Among them were corrosion of the metals, water uptake, limited potting time, and limited adhesion [8]. While corrosion of the metals and the water uptake could be reduced by measures concerning the recipe of the encapsulation, the potting time and the adhesion remain a bottleneck.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Practical data reveals that SG exhibits a TC and CTE of 0.17 W/(m⋅K) and 1000 ppm/K, respectively. On the other hand, EP demonstrates a TC of 1 W/(m⋅K) and a Tg of 135°C, as documented in [44]. This underscores the ongoing challenge of aligning encapsulant properties with the exacting requirements of advanced (U)WBG power modules.…”
Section: Ieee Transactions On Dielectrics and Electrical Insulationmentioning
confidence: 77%
“…It is observed that EPs are desired for power module packaging due to their higher dielectric strength (>20 kV/mm), lower water absorption rate (<0.1%), higher TC (>0.8 W/m-K), and lower CTE (<8/38 ppm/K). However, EPs' lower Tg (<135 o C) hinders their performance below 200 o C. Additionally, the viscosity of EPs (> 50 Pa.s) is significantly higher than SG and the desired limit of high-temperature encapsulant [44], [45]. This hinders the easy flow of the material in power modules, which leads to the formation of voids, bubbles, and defects that accelerate insulation aging.…”
Section: Ieee Transactions On Dielectrics and Electrical Insulationmentioning
confidence: 99%
“…In fact, the non-method above was economic or convenient to manufacture in nowadays industry practice. Anyway, our group got a new way to realize the manufacture of SiC for packaging material using at a very low producing temperature and could utilize at a high temperature [8][9][10] .…”
Section: Discussionmentioning
confidence: 99%